2018
DOI: 10.1016/j.ajpath.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor-7 Signaling Promotes Nonalcoholic Steatohepatitis by Inhibiting Regulatory T Cells in Mice

Abstract: Toll-like receptor 7 (TLR7) signaling regulates the production of type 1 interferons (IFNs) and proinflammatory cytokines, such as tumor necrosis factor (TNF)-α, implicated in the control of regulatory T (Treg) cell activity. However, the mechanistic interplay between TLR7 signaling and Treg cells in nonalcoholic steatohepatitis (NASH) has not been elucidated. Our aim was to clarify the role of TLR7 signaling in the pathogenesis of NASH. Steatohepatitis was induced in wild-type (WT), TLR7-deficient, IFN-α/β re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 52 publications
(48 reference statements)
0
18
0
1
Order By: Relevance
“…To establish an in vitro NASH model, primary HPs were treated with 0.4 mmol/L PA, as previously described. 21 Stock solutions of RSL-3, Lip-1, and SS were prepared and stored at À20 C. DFO was freshly prepared and dissolved in culture medium. Primary HPs were treated with the indicated concentration of these compounds.…”
Section: Isolation Of Primary Hpsmentioning
confidence: 99%
“…To establish an in vitro NASH model, primary HPs were treated with 0.4 mmol/L PA, as previously described. 21 Stock solutions of RSL-3, Lip-1, and SS were prepared and stored at À20 C. DFO was freshly prepared and dissolved in culture medium. Primary HPs were treated with the indicated concentration of these compounds.…”
Section: Isolation Of Primary Hpsmentioning
confidence: 99%
“…Toll-like receptor-7 signaling promotes NASH by inhibiting regulatory T cells in mice. 253 Memory CD4 + and CD8 + Tcell numbers are increased while naïve T-cell numbers are decreased in the peripheral blood of NAFLD patients. 254 Moreover, the number of infiltrating CD8 + T cells in the portal vein is elevated in NAFLD patients and is associated with the severity of hepatic inflammation.…”
Section: Microbial Dysbiosis and Intestinal Barrier Functionmentioning
confidence: 94%
“…In an experimental study of allergy, using several knockout models the authors showed that TLR7 activation resulted in IL-10 production in splenic B cells that in turn led to T reg expansion. However, in a recent paper by Roh et al [36] an antagonist is used to block TLR7 in studies of nonalcoholic steatohepatitis (NASH) and this treatment ameliorated disease. Taken together, further studies are required to pinpoint effects of TLR7 agonists versus antagonist in the T reg compartment.…”
Section: Discussionmentioning
confidence: 99%